The Place of Capitalist Self-Critique - Engster, Frank (Identities: Journal for Politics, Gender and Culture, 2022)
Critiques of capitalism are grounded in the quandary that their critics cannot locate a standpoint or place for an adequate determination nor scientific explanation of existing capitalist society; nor can they identify a standpoint for its replacement by non-capitalist society. Why does this quandary exist? Can we at least have some kind of ‘first’ standpoint of critique that is both given by capitalist society itself and at once adequate to it? “First” and “adequate” in the sense that it enables society to view itself as an external object in the first place and thus to make also its change an object? This paper shall show that through various stages of Marxist and post-Marxist thought a distinct shift is traceable. The place to criticize existing society and to turn its criticism into the idea of another society shifts from “elsewhere in space” to the immanent contradictions of capitalism and their social progress in time, to, finally, the suspension of time itself. To determine the quandary of critique, this paper argues that the place of critique in fact needs to be addressed in terms of temporality, but differently than in the legacy of Lenin, Luxemburg, Lukács and Gramsci through to Benjamin, Bloch etc. to current post-Marxism. Author(s): Frank Engster Title (English): The Place of Capitalist Self-Critique Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 8-26 Page Count: 18 Citation (English): Frank Engster, "The Place of Capitalist Self-Critique,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 8-26. Author Biography Frank Engster, Helle Panke Rosa-Luxemburg-Stiftung Berlin Frank Engster wrote his PhD thesis on the subject of time, money and measure. He is interested in the different — (post-)operaist, (post-)structuralist, form-analytic, (queer) feminist etc. — readings of Marx’s critique, especially in money as a technique and its connection with measurement, quantification, time and (natural) science. Some of his publications are on academia.edu.